Optimization of ultrasonic-assisted extraction of flavonoids from Lactuca indica L. cv. Mengzao and their antioxidant properties - Hao, Junfeng; Wang, Zhijun; Jia, Yushan; Sun, Lin; Fu, Zhihui; Zhao, Muqier; Li, Yuyu; Yuan, Ning; Cong, Baiming; Zhao, Lixing; Ge, Gentu (Frontiers in Nutrition, 2023)
In this study, the ultrasound-assisted extraction (UAE) conditions of flavonoids from L. indica L.cv. Mengzao was optimized, and the flavonoids content and their antioxidant potential in different parts were analyzed. The optimal extraction parameters to obtain the highest total flavonoid content (TFC) were a ratio of liquid to solid of 24.76 mL/g, ultrasonic power of 411.43 W, ethanol concentration of 58.86% and an extraction time of 30 min, the average TFC could reach 48.01 mg/g. For the yield of flavonoid, the UAE method had the best extraction capacity among the three methods. In general, the TFC in different parts of L. indica L.cv. Mengzao followed the order flower> leaf> stem> root, the flowering period is the most suitable harvesting period. From ultra-high performance liquid chromatography-mass spectrometry (UPLC-MS) quantification, the flower samples showed significantly higher six flavonoids and had the highest radical scavenging capacities compared to other samples. A high positive correlation was observed between the antioxidant activity and TFC of L. indica L.cv. Mengzao, luteolin-7-O-glucoside and rutin were significantly (p<0.05) correlated with all antioxidant evaluations. This study provides valuable information for the development and utilization of flavonoids in L. indica L.cv. Mengzao as ingredients in food, feed and nutritional health products.